Obesity, metabolic syndrome, and cancer: pathophysiological and therapeutic associations - Mili, Nikoletta; Paschou, Stavroula A.; Goulis, Dimitrios G.; Dimopoulos, Meletios-Athanasios; Lambrinoudaki, Irene; Psaltopoulou, Theodora (Endocrine, 2021)
Overweight, obesity, and metabolic syndrome (MetS) have become epidemic conditions affecting 39%, 13%, and 20% of the population respectively. The aim of this article is to review the literature on the association of obesity and MetS with the risk of cancer. We also explore the effect of lifestyle modifications, such as diet, physical activity, and antidiabetic medications, on cancer incidence. Increased body mass index (BMI) has been associated with a multitude of site-specific cancers, reaching relative risk (RR) 1.54 [95% confidence interval (CI) 1.47–1.61] per 5 unit increase for endometrial cancer, as well as with overall cancer risk (RR 1.03, 95% CI 1.02–1.05). Central adiposity measured by waist circumference or waist-to-hip ratio has been suggested as a stronger predictor than BMI for several cancers, such as colorectal cancer. Metabolic Syndrome has been consistently and positively associated with the risk of very common cancers like colorectal (RR 1.34, 95% CI 1.24–1.44), endometrial (RR 1.62, 95% CI 1.26–2.07) and postmenopausal breast cancer (RR 2.01, 95% CI 1.55–2.60). Hyperglycemia and subsequently T2DM have been also shown to increase the risk of cancer. Nevertheless, these risk factors are modifiable and therefore implementing lifestyle modifications could prevent an important number of cancer cases. Adherence to cancer prevention guidelines, including maintaining a healthy weight, having regular physical exercise (RR 0.58–0.90 for different cite specific cancers) and following a healthy dietary pattern (RR 0.74–0.94 for different cite specific cancers) have a protective effect on the risk of cancer. The strength of this review is the presentation of the best evidence, as the data derive mainly from meta-analyses. Public health policies should focus on the modification of risk factors and future research is needed to reveal the pathophysiological links between these risk factors and cancer to develop more efficient prevention and treatment strategies.